Characterization and Mycotoxin Screening of Fungal Isolates from Palm Sugar - Monisha K.; Mariyanancyarputha L (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2022)
The global demand for alternative sugars is rising due to their lower glycemic index and other health benefits. However, improper manufacture, processing, transport, export, and/or marketing of regional sugar products increases the risk of microbial infection upon consumption. Fungal exposure and contamination of alternative sugars may occur as a result of enhanced hygroscopicity of certain sugar forms such as coconut and palm sugars, which strongly attract water molecules to their surface and thereby fungal spores, a property affected by adulteration practices, e.g. incorporation of cane sugar. The present study highlights risks of unregulated processing of palm sugar in the form of fungal contaminants and their toxigenic potential. Palm sugar was sampled for fungal isolates which were identified as Aspergillus flavus, A. niger, A. carbonarius, A. terreus, and A. fumigatus, followed by colony enumeration. Subsequent extraction of fungal extracts by thin layer chromatography resulted in detection of mycotoxins, including aflatoxins B1 and G1, citrinin, and ochratoxin. The findings confirmed that humid conditions may be optimal for the presence of toxigenic fungi in the palm sugar and production of toxic metabolites, indicating that more stringent regulation is required for palm sugar processing, as the toxins can lead to detrimental health consequences, including acute poisoning, nephropathy, and liver cancer.